Pelatihan Tech for Kids Memperkenalkan STEM untuk Mengembangkan Kemampuan Kepemimpinan Siswa di Era Industri 4.0 - Deny Nusyirwan; Eko Prayetno; Sapta Nugraha; Harits Aditya Nugraha; Muhammad Andika; Muhammad Abyan Fadillah (Universitas Muhammadiyah Semarang, 2020)
The industry is currently undergoing a transformation towards full digitization and intelligence of the manufacturing process, which is called the Fourth Industrial Revolution or Industry 4.0. Visionary but fairly realistic concepts such as Internet of Things, Cloud-based Manufacturing and Smart Manufacturing applications. Although there is mutual agreement on the need for advancement in production technology and business models in the Industry 4.0 sense, the main obstacle lies in the perception of complexity and abstractness which partially hinders its rapid transformation into industrial practice. The term